Health Literacy, Health Outcomes, and the Caregiver Role in Traumatic Brain Injury - Hahn, Elizabeth A. (Rehabil Psychol, 2020)
PURPOSE/OBJECTIVE: The purpose of this study is to estimate the occurrence of low health literacy among caregivers of people with traumatic brain injury (TBI), and to evaluate associations of health literacy with caregiver health-related quality of life (HRQOL) and perceptions of the caregiving role. RESEARCH METHOD/DESIGN: The TBI-CareQOL measurement system assesses important self-reported outcomes for caregivers of civilians or service members/veterans (SMVs) with TBI. The validation phase included the Health Literacy Assessment Using Talking Touchscreen Technology (Health LiTT) measure. Multivariable regression evaluated the impact of low health literacy on generic and TBI-specific HRQOL and appraisals of the caregiving role, adjusted for caregiver gender, race/ethnicity and education, and the functional status of the TBI care recipient. RESULTS: Among 131 caregivers, 28 (21%) had low health literacy. Compared with the high health literacy group, the group with low health literacy had fewer women, more racial/ethnic minorities, and lower education (all p < .05). The low health literacy group reported more subjective caregiving burden, less satisfaction with their relationship with the TBI recipient, less caregiving mastery, and poorer physical health (all p < .05). There were no differences between health literacy groups in caregiving ideology, caregiver-specific HRQOL or general mental health. CONCLUSIONS/IMPLICATIONS: A better understanding of the links between health literacy and caregiver HRQOL and the caregiving role can help identify strategies to meet the needs of this underserved population. Tailored interventions for caregivers with low health literacy could improve outcomes for both the caregiver and the care recipient.